If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9=3(x+1)+6
We move all terms to the left:
-9-(3(x+1)+6)=0
We calculate terms in parentheses: -(3(x+1)+6), so:We get rid of parentheses
3(x+1)+6
We multiply parentheses
3x+3+6
We add all the numbers together, and all the variables
3x+9
Back to the equation:
-(3x+9)
-3x-9-9=0
We add all the numbers together, and all the variables
-3x-18=0
We move all terms containing x to the left, all other terms to the right
-3x=18
x=18/-3
x=-6
| 4x+61=13 | | 6b+1=1+3b | | X^2-10x-10X=0 | | 4(z^2+4z-3)=0 | | 85=-2x+5 | | 3u–38=34 | | 3/4=9/x+8 | | u/7=11.2 | | A=C(0.5)^2/k | | 4x(2x-9)=5(6-x) | | -80 = p-6+ -71 | | 2k^2+7k-10=0 | | f-4+2=5 | | 2/3x+5=14 | | 4+1-3n+8=5n-7-3n | | (D3+3D2-4)y=0 | | 1-2z=-13 | | 8t–18=46 | | 1/5(25-5a=4-a | | 7x^2+111=0 | | 4(v+5)=84 | | 2x^-6x-93=0 | | d/8+9=13 | | –1/4a-4=7/4a-3 | | 3(x-1)-4x=5-2(x+1)3) | | q/6+28=32 | | -4=6/7v | | -19x=84 | | 22n-21-14=-21 | | 2+2y=20 | | 35(x−7)=1 | | 6n+2=-4n+12 |